If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + -29 = 3z + -8 Reorder the terms: -29 + 6z = 3z + -8 Reorder the terms: -29 + 6z = -8 + 3z Solving -29 + 6z = -8 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. -29 + 6z + -3z = -8 + 3z + -3z Combine like terms: 6z + -3z = 3z -29 + 3z = -8 + 3z + -3z Combine like terms: 3z + -3z = 0 -29 + 3z = -8 + 0 -29 + 3z = -8 Add '29' to each side of the equation. -29 + 29 + 3z = -8 + 29 Combine like terms: -29 + 29 = 0 0 + 3z = -8 + 29 3z = -8 + 29 Combine like terms: -8 + 29 = 21 3z = 21 Divide each side by '3'. z = 7 Simplifying z = 7
| 3(3x-3)y=32 | | 6c-17=3c-35 | | 9z-24=5z-8 | | 60=13m+a | | 4x+6=-x+36 | | logE=17.8 | | 6y-5x-5=6(xy)-5 | | (-3a-b)+(2a-5b)= | | 8888=500 | | 2-3y=px | | 18-Y=(-18) | | 10z-93=4z-45 | | 4g-11=13-2g | | 5a+6=3a+10 | | y-13=36 | | 3(4f-7)=-45 | | 10x^(1/3)-10x | | 8-5q=23 | | 5x+11=2x+38 | | -1+6c=11 | | -8+9c=10 | | 9x+13=4x+48 | | 17x+5=56 | | -9b+2=-7 | | 6x-1+6x=7 | | -5b+8=-32 | | 3x+py=6 | | 2x+4.1=3.9 | | 8x-11=6x+2 | | 5a+4=-26 | | 3(c+4)-c=6 | | 8h-5=h-5 |